2022
DOI: 10.1073/pnas.2200016119
|View full text |Cite
|
Sign up to set email alerts
|

Insights into bear evolution from a Pleistocene polar bear genome

Abstract: The polar bear ( Ursus maritimus ) has become a symbol of the threat to biodiversity from climate change. Understanding polar bear evolutionary history may provide insights into apex carnivore responses and prospects during periods of extreme environmental perturbations. In recent years, genomic studies have examined bear speciation and population history, including evidence for ancient admixture between polar bears and brown bears ( Ursus arctos ). Here, we exte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 62 publications
3
23
0
Order By: Relevance
“…Our nuclear SNPs phylogenetic results indicated that all North American brown bears shared the same ancestry, which is consistent with recent studies (de Jong et al, 2023; Lan et al, 2022). MtDNA phylogeography studies suggest that brown bears in North America arrived in three different temporal migration waves from Asia ~34–279 kya, representing clades 2a, 3 (subclades 3a and 3b) and 4 (Anijalg et al, 2018; Miller et al, 2006; Waits et al, 1998).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our nuclear SNPs phylogenetic results indicated that all North American brown bears shared the same ancestry, which is consistent with recent studies (de Jong et al, 2023; Lan et al, 2022). MtDNA phylogeography studies suggest that brown bears in North America arrived in three different temporal migration waves from Asia ~34–279 kya, representing clades 2a, 3 (subclades 3a and 3b) and 4 (Anijalg et al, 2018; Miller et al, 2006; Waits et al, 1998).…”
Section: Discussionsupporting
confidence: 92%
“…The use of multiple biparentally inherited nuclear microsatellite loci has been effective for evaluating contemporary population structure, connectivity and demography, but such data provide limited information about global evolutionary relationships, genetic diversity and historical demography of this species (Paetkau et al, 1998; Waits & Paetkau, 2005). Genomic data have been extremely useful for delineating taxonomic units among brown bears (Hailer et al, 2012; Miller et al, 2012), despite earlier confounding factors caused by hybridization and introgression between brown and polar bears (Cahill et al, 2015; Lan et al, 2022; Miller et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Our results show that significantly negative f3 values reflected close phylogenetic relationships among samples, as anticipated based on previous studies 16 . Crosses of negative values in our f3 heat maps (wherein all source combinations showed negative f3) likely reflected strong identity by descent (IBD), as also seen in other organisms, such as Syzygium 22 and Ursus 61 . For example, the two representatives of Phyllostegia warshaueri was marked by the cross pattern of negative values when one was configured as a target and the other as a source (Supplementary Fig.…”
Section: The Majority Of Present-day Hawaiian Mints Appear Unadmixedmentioning
confidence: 57%
“…One proposed hypothesis concerning their origin has been referred to as the ‘population conversion theory’, which places a brown bear‐polar bear hybrid origin of ABC brown bears to after the LGM (Cahill et al, 2013). Recently, however, genome sequence analyses, including from an ancient polar bear, and statistical fitting of data to alternative admixture graph scenarios instead favoured an ancient introgression from brown bears into the ancestor of polar bears, possibly dating back over 150,000 years (Lan et al, 2022; Miller et al, 2012), although the issue of gene flow, and its timing and direction, between the two species continues to be debated (de Jong et al, 2023; Wang et al, 2022). It is possible that the ABC haplotype may once have represented a geographically more widespread lineage, also occurring in the more southernly Haida Gwaii archipelago at least from around 14.7 until 12.7 cal kyr B.P.…”
Section: Discussionmentioning
confidence: 99%
“…DNA from all samples was target‐enriched using a custom‐designed ursid mitogenome bait panel (Lan et al, 2017). In addition, to test the application of whole genome enrichment (WGE) on these specimens, WGE was performed for three samples (UAMES 53085, UAMES 53102 and UAMES 53123) following the protocol described in Lan et al (2022). Both methods followed the standard mybaits v. 3.0 protocol, with equal masses of libraries pooled, bead‐templated and sequenced using the Ion PI Chip Kit v2 chemistry and sequenced on the Ion Proton platform.…”
Section: Methodsmentioning
confidence: 99%